Використання баз даних при створенні інтернет-магазинів - Свічкар, В. Є.; Утва, В. О.; Кушельман, Є. О. (ХНУРЕ, 2024)
My role in the development of the online store is to create the database architecture and design the database schema that will represent all the necessary entities, relations and attributes necessary for the store to function effectively. In today's digital economic environment, where competition in the e-commerce market is increasing every day, effective data management is a critical success factor for online stores. Databases ensure reliable storage and organization of information about products, customers and transactions, contributing to the automation of business processes, personalization of customer service, data analysis and strategic decision-making. Thus, the development and effective use of databases become key tasks for ensuring the competitiveness and stable functioning of online stores in the modern business environment.
Keywords: створення інтернет-магазинів; інтернет-магазин